Rescue Strategy for Covid Heroes in Households: Reconstructing the Meaning of Hadith Ahkam in Sunan Abū Dāwud - Hasanah, Uswatun (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
Work from Home (WfH) and online schooling as a policy to reduce the risk of the spread of COVID 19 has an impact on increasing the risk of fatigue and stress for women. Especially for working women who are married and have children. While men can focus on completing office tasks at home, this is not the case for women. The economic movement of the family that slows down while domestic needs and responsibilities increase both in quantity and quality is a severe phenomenon that haunts the lives of women. Therefore, it is necessary to reconstruct the understanding of the meaning of the Prophet's hadith which contains the law as an argument which becomes the basic principle of the implementation of Islamic law. The method used in this research is the maudhui method, focusing on the hadith ahkam narrated by Abū Dāwud number 236 which explains the concept of partnership between men and women in household responsibilities. Content analysis is used as a data analysis technique. The hadith text is a basic legal reference for the principle of equality between men and women. Both have the same rights as human beings. The right to live with dignity, religion, politics, activities in the social, economic and educational spheres as well as the right and responsibility to take care of the household and obey the law. Not respecting women's rights means denying the law, which is the principle of equality in the hadith text. Taking care of the household is a job that can be learned and can also be done together. This is done as an effort to recognize and save women as household heroes from the increased risk of fatigue and stress, especially in difficult times.